Enhancement Mode (E-Mode) AlGaN/GaN MOSFET With 10(-13) A/mm Leakage Current and 10(12) ON/OFF Current Ratio - Xu, Zhe; Wang, Jinyan; Yong Cai; Liu, Jingqian; Jin, Chunyan; Yang, Zhenchuan; Wang, Maojun; Min Yu; Xie, Bing; Wu, Wengang; Ma, Xiaohua; Zhang, Jincheng; et al. (IEEE ELECTRON DEVICE LETTERS, 2014)
Postgate annealing (PGA) in N-2/O-2 atmosphere at 300 degrees C for various annealing time is performed on enhancement mode AlGaN/GaN MOSFET fabricated using a self-terminating gate recess etching technique. After 45-min annealing, the device OFF-state leakage current decreases by more than two orders of magnitude and thus a low OFF-state leakage current of similar to 10(-13) A/mm is obtained at room temperature, resulting in an excellent ON/OFF current ratio of similar to 10(12). At 250 degrees C, the device still exhibits a low OFF-state leakage current of similar to 10(-9) A/mm and high ON/OFF current ratio of similar to 10(8). Meanwhile, a strong correlation between the OFF-state leakage current and mesa isolation current is observed as we change the annealing time: 1) the lower the mesa isolation current and 2) the lower the OFF-state leakage current and thus the higher the ON/OFF current ratio. It is the suppression of the mesa isolation current owing to the passivation of atomic layer deposition Al2O3 that leads to the improvement of the OFF-state leakage current and ON/OFF current ratio after PGA. Besides, the device shows no obvious change in terms of its threshold voltage and maximum drain current after PGA.